2013
DOI: 10.1007/s00520-013-1744-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in critically ill chronic lymphocytic leukemia patients

Abstract: Acute pulmonary infections remain the leading cause of ICU admission in patients with CLL. The severity at ICU admission and past history of infection were the only factors associated with hospital mortality. Neither disease characteristics nor previous cancer treatments were associated with outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The characteristics of the 46 included studies are described in eTable 1 (http://links.lww.com/CCX/B54). Most of the published literature was from Europe ( n = 18) (15–32), followed by Asia ( n = 12) (33–44), North America ( n = 9) (4, 45–52), South America ( n = 5) (5, 53–56), and Oceania ( n = 2) (57, 58). On the other hand, studies from North America contributed the highest number of patients ( n = 37,255), followed by South America ( n = 32,723), Asia ( n = 23,540), Europe ( n = 16,149), and Oceania ( n = 478).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 46 included studies are described in eTable 1 (http://links.lww.com/CCX/B54). Most of the published literature was from Europe ( n = 18) (15–32), followed by Asia ( n = 12) (33–44), North America ( n = 9) (4, 45–52), South America ( n = 5) (5, 53–56), and Oceania ( n = 2) (57, 58). On the other hand, studies from North America contributed the highest number of patients ( n = 37,255), followed by South America ( n = 32,723), Asia ( n = 23,540), Europe ( n = 16,149), and Oceania ( n = 478).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported data on length of stay in the ICU (4, 5, 16–19, 21, 23–25, 28, 29, 32–36, 38–52, 54–58). The WM length of stay was 5.9 days (95% CI, 5.3–6.5 d), and the median was 5.7 days (range, 2.7–23.7 d).…”
Section: Resultsmentioning
confidence: 99%